WEB APPLICATION FOR SERVICE SALE OF COMPUTER TECHNICS DEVELOPED USING FRAMEWORKS YII2 (Modern information system and technologies, 2018)
The article presents a web application for the sale of computer equipment. The functions and principles of the main components of the service are revealed. Keywords: Keywords: web application, IT sphere, sales service, MVC representation model, YII2 frameworks, PHP programming language.